Revival and reform in Mary Tudor's Church: a question of money - Pogson, R. H. (The journal of ecclesiastical history, 1974)
In explaining the failure of Mary Tudor's plans for Catholic revival during her reign, it is customary to dwell on her manifold errors of judgment. No one can deny her ardent desire to restore the love for Rome among her subjects—she declared that her people's souls meant more to her than ten kingdoms; but she is remembered for burning heretics and thus providing English Protestantism with much-needed martyrs and respectability, rather than for inspiring Counter-Reformation zeal. The most obvious reason for this failure was Mary's early death, which left her little time for long-term policies; but in addition emphasis must be placed on her misunderstanding of her subjects' prejudices and confusion after the schism. She disgusted the strong Henrician national feeling by marrying a foreigner and delighting openly in her Spanish blood; she showed no sympathy for the financial worries of influential subjects who had obtained monastic property and had no wish to surrender it; she instigated a persecution which aroused distaste even in minds accustomed to sixteenth century suffering and punishment; and she embarked on an unpopular war and lost Calais disastrously. Moreover, she reposed greatest trust in Reginald Pole, the papal legate, another leader who failed to comprehend the bitterness of English xenophobia and the strength of anticlericalism and heresy. Pole assumed that anti-Roman sentiments were the shortlived results of schismatic sin and would fade with the orderly restoration of Roman rule; and so he did not even begin to build a militant organisation which could have tried to resist Elizabethan Protestantism. It is an impressive catalogue of mistakes.